A method for determining the bonding strength of glass fibers and resins
Patent Information
- Application Number
- CN202410080148.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-19
AI Technical Summary
这样的情况则制约了玻璃纤维及其复合材料性能的发展
[0023]本发明根据玻璃纤维表面浸润剂分离的难易程度,将玻璃纤维表面的浸润剂划分为:自由组份,亚稳组份和键合组份。其中,自由组份是可以通过溶剂短时间浸泡分离的组份,最容易分离得到;亚稳组份则是通过溶剂索氏提取分离的组份;键合组份是通过硅烷偶联剂桥接的组份,通过热水使硅烷偶联剂水解才能提取。通过测试玻璃纤维与树脂的横向纤维束拉伸强度,从而判断自由组份含量、亚稳组份含量与键合组份含量对玻璃纤维和树脂的结合强度的影响,为制备高性能复合材料以及提升玻璃纤维的机械性能提供理论指导。
Smart Images

Figure HDA0004672880000000011 
Figure HDA0004672880000000012
Abstract
Description
Technical Field
[0001] This invention belongs to the field of glass fiber, and specifically relates to a method for determining the bonding strength between glass fiber and resin. Background Technology
[0002] Continuous large-scale glass fiber production involves melting ore raw materials at high temperatures in a furnace to form molten glass, which is then drawn, sized, bundled, wound, and dried through a platinum-rhodium alloy metal spinneret to form glass fiber products. In glass fiber production, sizing with sizing agents plays a crucial role in the mechanical properties of the fibers and their composites. The sizing agent primarily functions as a lubricant and protectant, a binder and bundler, and a bonding agent at the fiber-resin interface.
[0003] Glass fiber sizing agents are multi-component mixtures, whose main components include coupling agents, film-forming agents, antistatic agents, and lubricants. Each component has a different function for the glass fiber. The film-forming agent is the most abundant component in the sizing agent, while the coupling agent binds to the glass fiber surface through silanol groups, acting as a bridge connecting the glass fiber and the sizing agent / resin molecules. The sizing agent forms different components on the glass fiber surface, each with different functions; some components chemically bond with the glass fiber, while others simply accumulate on the glass fiber surface.
[0004] However, commercial glass fiber sizing agents are multi-component mixtures including film-forming agents, coupling agents, antistatic agents, and lubricants. The structure formed by the sizing agent on the glass fiber surface is unknown, making it difficult for researchers to clearly understand the complex components of the sizing agent on the glass fiber surface. Furthermore, the impact of different production processes (including sizing agent components, glass fiber drying temperature, and glass fiber drying time) on these complex components is difficult to determine. Therefore, it is difficult to improve the complex components of the sizing agent on the glass fiber surface through production process control, thereby further controlling the bonding strength between the glass fiber and the resin. This situation restricts the development of the properties of glass fibers and their composites. Therefore, it is necessary to separate the complex sizing agent components on the glass fiber surface, determine the sizing agent content, and clarify the influence of different sizing agent component contents on the interfacial bonding strength of composite materials, thereby improving the bonding strength between glass fibers and resin and preparing high-performance composite materials. Summary of the Invention
[0005] To overcome the problems in the prior art, the purpose of this invention is to provide a method for determining the bonding strength between glass fiber and resin. This method can accurately determine the content of the sizing agent on the surface of the glass fiber, which is beneficial for studying the relationship between the glass fiber sizing agent and the bonding strength between the glass fiber and resin, thereby improving the bonding strength between the glass fiber and resin and preparing high-performance composite materials.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A method for determining the bond strength between glass fiber and resin includes the following steps:
[0008] (1) Dry the glass fiber coated with sizing agent to obtain dried glass fiber 1; place the dried glass fiber at 620℃ for 1 hour, and the mass loss before and after calcination is the mass of sizing agent;
[0009] (2) The dried glass fiber 1 is soaked in a low-boiling-point organic solvent and then dried to obtain glass fiber 2. The mass difference between glass fiber 2 and dried glass fiber 1 divided by the mass of the sizing agent is the free component content.
[0010] (3) Glass fiber 2 is extracted by Soxhlet and then dried to obtain glass fiber 3. The mass difference between glass fiber 3 and glass fiber 2 is divided by the mass of the sizing agent to obtain the content of metastable component.
[0011] (4) After soaking glass fiber 3 in hot water, it is dried to obtain glass fiber 4. The difference in mass between glass fiber 4 and glass fiber 3 divided by the mass of sizing agent is the content of bonding component.
[0012] (5) Test the transverse fiber bundle tensile strength of one of glass fiber 1, glass fiber 2, glass fiber 3 and glass fiber 4 with resin, and determine the influence of free component content, metastable component content and bonding component content on the bonding strength between glass fiber and resin.
[0013] Furthermore, in step (1), the drying temperature is 110-130℃ and the time is 19-23 hours.
[0014] Furthermore, in step (1), the diameter of the glass fiber monofilament is 8-30 μm.
[0015] Furthermore, in steps (2) and (3), the low-boiling-point organic solvent is acetone, n-hexane, dichloromethane, chloroform, tetrahydrofuran, ethanol, or methanol.
[0016] Furthermore, in step (2), the soaking time is 10-100 minutes.
[0017] Furthermore, in step (3), the Soxhlet extraction time is 2-48 hours.
[0018] Furthermore, in step (4), the temperature of the hot water is 80-100℃, and the soaking time is 1-10 hours.
[0019] Furthermore, the process for testing the transverse fiber bundle tensile strength of each of glass fibers 1, 2, 3, and 4 with the resin is as follows: epoxy resin is mixed with polyetheramine to obtain pre-cured resin. Glass fibers 1, 2, 3, or 4 are placed in the middle position, and pre-cured resin is placed on both sides of glass fibers 1, 2, 3, or 4. Then, the mixture is cured to obtain a composite material specimen. The transverse fiber bundle tensile test is performed on the composite material specimen.
[0020] Furthermore, the mass ratio of epoxy resin to polyetheramine is 100:55.
[0021] Furthermore, the curing process is as follows: keep at 100℃ for 1 hour, then keep at 140℃ for 1 hour, and finally keep at 180℃ for 2 hours.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] This invention classifies the wetting agents on the glass fiber surface into three categories based on the ease of separation: free components, metastable components, and bonded components. Free components are those that can be separated by short-term solvent immersion and are the easiest to obtain. Metastable components are those that can be separated by Soxhlet extraction. Bonded components are those bridged by silane coupling agents, which require hot water to hydrolyze the silane coupling agents for extraction. By testing the transverse fiber bundle tensile strength of the glass fiber and resin, the influence of the free component content, metastable component content, and bonded component content on the bonding strength between the glass fiber and resin is determined, providing theoretical guidance for the preparation of high-performance composite materials and the improvement of the mechanical properties of glass fibers.
[0024] Furthermore, this invention employs solvent extraction, controlling the solvent, extraction time, and extraction method to separate the complex molecular network on the glass fiber surface. The separated wetting agent is collected by rotary evaporation or freeze-drying for chemical structure analysis, thereby confirming whether different components of the wetting agent are bonded to the glass fiber surface. Components separated by acetone within a short time, without bonding or non-covalent interactions with the glass fiber, are defined as free components; components separated by long-term Soxhlet extraction, exhibiting non-covalent interactions with the glass fiber surface, are defined as metastable components; components bonded by silane coupling agents, which hydrolyze in water and are extracted by hot water, are defined as bonded components. The bonded components on the glass fiber surface can regulate surface cracks, prevent stress concentration, and improve the mechanical properties of the glass fiber; furthermore, they can form an interpenetrating network with the resin structure in the composite material, strengthening the fiber-resin interface. This invention utilizes solvent separation of the sizing agent to determine the content of different components of the sizing agent on the glass fiber surface. This helps researchers and production personnel assess the impact of different production processes (temperature, humidity, drying time, etc.) on the content of these different components. Furthermore, it allows for the evaluation of the influence of different sizing agent component contents on the bonding strength between the glass fiber and resin, helping researchers clarify the effect of varying sizing agent component contents on this bonding strength. Attached Figure Description
[0025] Figure 1 The results show the content of the surface sizing agent on the glass fiber and the test results of the transverse fiber bundle tensile strength of the glass fiber / resin in this invention. Wherein, a represents the content of different components of the surface sizing agent on the glass fiber dried at 125℃, b represents the transverse fiber bundle tensile strength of the glass fiber / resin dried at 125℃, c represents the content of different components of the sizing agent dried at 115℃, and d represents the transverse fiber bundle tensile strength of the glass fiber / resin dried at 115℃.
[0026] Figure 2 These are the test results of the glass fiber surface sizing agent content and the transverse fiber bundle tensile strength of the glass fiber / resin in this invention. Wherein, a represents the content of different components of the glass fiber surface sizing agent after drying at 125℃ for 19 hours, b represents the transverse fiber bundle tensile strength of the glass fiber / resin after drying at 125℃ for 23 hours, c represents the content of different components of the sizing agent after drying at 125℃ for 19 hours, and d represents the transverse fiber bundle tensile strength of the glass fiber / resin after drying at 125℃ for 23 hours. Detailed Implementation
[0027] The technical solution of the present invention is described in detail below with reference to the accompanying drawings. The embodiments of the present invention are for illustrative purposes only, and the scope of the method is not limited by the embodiments.
[0028] The present invention provides a method for determining the bonding strength between glass fiber and resin, comprising the following steps:
[0029] (1) Glass raw materials are melted, drawn, and cooled by spraying water mist to obtain glass fiber filaments with a diameter of 10-60 μm. Immediately afterwards, the glass fiber filaments are sized with an epoxy-based glass fiber sizing agent. Then, the sized glass fiber filaments are bundled together by a bundling wheel to form a complete glass fiber bundle. The resulting glass fiber bundle is then wound into a roll at high speed to obtain an epoxy-based glass fiber yarn roll containing a large amount of moisture and sizing agent.
[0030] The epoxy-based glass fiber sizing agent used in this invention is manufactured by China Taishan Glass Fiber Co., Ltd. The epoxy-based glass fiber sizing agent itself is a white emulsion.
[0031] (2) Place the epoxy-based glass fiber yarn roll containing a large amount of moisture and sizing agent in a drying oven (the type of drying oven is a hot air drying oven) and dry it with hot air at 110-130℃ for 19-23 hours, so that the moisture in the epoxy-based glass fiber yarn roll evaporates and the epoxy emulsion particles form a film, and glass fiber 1 is obtained; place the dried glass fiber in a muffle furnace at 620℃ for 1 hour, and weigh the glass fiber before and after calcination with an electronic balance. The mass loss before and after calcination is the total mass of sizing agent.
[0032] (3) Soak glass fiber 1 in a low-boiling-point organic solvent for 10-100 minutes, then dry it in an oven to remove the organic solvent, and obtain glass fiber 2. Weigh the glass fiber (glass fiber 1 and glass fiber 2) before and after soaking using an electronic balance. Subtract the mass after soaking from the mass before soaking to obtain the mass difference. Then remove the low-boiling-point organic solvent by rotary evaporation and collect the retrievable substance 1 on the surface of the glass fiber. Define the retrievable substance 1 on the surface of the glass fiber as the free component of the sizing agent on the surface of the glass fiber. Divide the mass difference by the total mass of the sizing agent to obtain the content of the free component.
[0033] The low-boiling-point organic solvent is acetone, n-hexane, dichloromethane, chloroform, tetrahydrofuran, ethanol, or methanol, etc.
[0034] (4) Place glass fiber 2 in a Soxhlet extractor and extract for 2-48 hours using a low-boiling-point organic solvent. After extraction, dry the glass fiber 3 in an oven to remove the organic solvent. Weigh the glass fiber (glass fiber 2 and glass fiber 3) before and after Soxhlet extraction using an electronic balance. Subtract the mass after soaking from the mass before soaking to obtain the mass difference. Remove the low-boiling-point organic solvent by rotary evaporation and collect the retrievable substance 2 on the surface of the glass fiber. Define the retrievable substance 2 on the surface of the glass fiber as the metastable component of the glass fiber surface wetting agent. Divide the mass difference by the total mass of the wetting agent to obtain the content of the metastable component.
[0035] (5) Soak glass fiber 3 in hot water at 80-100℃ for 1-10 hours; after completion, dry it in an oven to remove moisture and obtain glass fiber 4. Weigh the glass fiber (i.e. glass fiber 3 and glass fiber 4) before and after soaking using an electronic balance. Subtract the mass after soaking from the mass before soaking to obtain the mass difference; remove moisture by freeze drying and collect the retrievable substance 3 on the surface of the glass fiber; define the retrievable substance 3 on the surface of the glass fiber as the bonding component of the sizing agent on the surface of the glass fiber. Divide the mass difference by the total mass of the sizing agent to obtain the content of the bonding component.
[0036] (6) Test the transverse fiber bundle tensile strength of glass fiber and resin to determine the influence of the sizing agent on the bonding strength between glass fiber and resin. That is, this invention judges the bonding strength between glass fiber and resin by the level of transverse fiber bundle tensile strength. Specifically, epoxy resin and polyetheramine are mixed at a mass ratio of 100:55 to obtain pre-cured resin. Glass fiber 1, glass fiber 2, glass fiber 3 or glass fiber 4 are placed in the middle position, and pre-cured resin is placed on both sides of glass fiber 1, glass fiber 2, glass fiber 3 or glass fiber 4. Then, the mixture is kept at 100℃ for 1 hour, then at 140℃ for 1 hour, and finally at 180℃ for 2 hours to cure, obtaining a composite material sample. The transverse fiber bundle tensile strength of the composite material sample is tested and recorded. By comparing the transverse fiber bundle tensile strength of different fibers with the content of free component / metastable component / bonding component of the sizing agent, the influence of different component contents of the sizing agent on the bonding strength between glass fiber and resin is determined.
[0037] (7) Compare the contents of free components, metastable components, and bonded components of glass fibers prepared by different drying processes, as well as the transverse fiber bundle tensile strength of glass fibers and resins.
[0038] In this invention, a Soxhlet extractor and a heating and cooling device are used to extract the wetting agent from the surface of glass fibers. During the solvent separation of the complex molecular structure of the wetting agent on the glass fiber surface, the glass fiber is placed in the Soxhlet extractor, and the solvent in the lower round-bottom flask is heated, evaporated, condensed, and refluxed back into the Soxhlet extractor to separate the wetting agent from the surface of the glass fibers.
[0039] The following are specific examples.
[0040] Example 1
[0041] A method for determining the bond strength between glass fiber and resin includes the following steps:
[0042] (1) After melting, drawing, and cooling the glass raw material with water mist, glass fiber filaments with a diameter of approximately 16 μm are obtained. Immediately afterwards, the glass fiber filaments are sized with an epoxy-based glass fiber sizing agent. Then, the sized glass fiber filaments are bundled together using a bundling wheel to form a complete glass fiber bundle. The resulting glass fiber bundle is then wound into a roll at high speed to obtain an epoxy-based glass fiber yarn roll containing a large amount of moisture and sizing agent.
[0043] (2) The epoxy-based glass fiber yarn roll containing a large amount of moisture was dried at 125℃ for 20h to obtain dried glass fiber; the dried glass fiber was placed in a muffle furnace at 620℃ for 1 hour, and the mass of the glass fiber before and after calcination was weighed by an electronic balance. The mass loss before and after calcination was the total mass of the impregnating agent.
[0044] (3) Soak the dried glass fiber in acetone for 100 minutes, then dry it in an oven to remove the acetone, obtaining acetone-soaked glass fiber. Weigh the glass fiber before and after soaking using an electronic balance. Subtract the mass after soaking from the mass before soaking to obtain the mass difference. Divide the mass difference by the total mass of the sizing agent to obtain the free component content.
[0045] Acetone is removed by rotary evaporation, and the free components of the glass fiber surface wetting agent are collected. The free components of the glass fiber surface wetting agent typically include film-forming agents, lubricants, and antistatic agents.
[0046] (4) The glass fibers soaked in acetone were extracted in a Soxhlet extractor for 24 hours using acetone as the solvent. After extraction, the acetone was removed by drying in an oven to obtain the Soxhlet-extracted glass fibers. The mass of the glass fibers before and after Soxhlet extraction was weighed using an electronic balance. The mass difference was obtained by subtracting the mass after soaking from the mass before soaking. The mass difference divided by the total mass of the sizing agent was the content of the metastable component. The low-boiling-point organic solvent was removed by rotary evaporation, and the metastable component of the sizing agent on the glass fiber surface was collected. The metastable component of the sizing agent on the glass fiber surface is usually an oligomeric silane coupling agent and a film-forming agent that interacts non-covalently with the coupling agent.
[0047] (5) Soxhlet-extracted glass fibers are soaked in hot water at 100°C for 3 hours; after completion, they are heated in an oven at 120°C for 2 hours to remove moisture, obtaining water-extracted glass fibers. The mass of the glass fibers before and after soaking is weighed using an electronic balance. The mass difference is obtained by subtracting the mass after soaking from the mass before soaking. The mass difference divided by the total mass of the sizing agent is the content of the bonding component; moisture is removed by freeze drying, and the bonding component of the sizing agent on the glass fiber surface is collected; the bonding component on the glass fiber surface is usually a coupling agent.
[0048] Example 2
[0049] Similar to Example 1, except that in step (2), the epoxy-based glass fiber yarn roll containing a large amount of moisture is dried at 115°C for 20 hours to obtain glass fibers dried at different drying temperatures.
[0050] This invention compares glass fiber products dried at 115°C and 125°C from China Taishan Glass Fiber Co., Ltd., to determine the effect of drying temperature on the surface sizing agent composition of glass fiber and the bonding strength between glass fiber and resin.
[0051] Figure 1 The sizing agent content of glass fiber surfaces dried at 115℃ and 125℃ respectively ( Figure 1 (a and c) and the tensile strength of glass fiber / resin transverse fiber bundles ( Figure 1 (b and d).
[0052] Specifically, experiments can first determine the content of free, metastable, and bonded components of the sizing agent on the surface of different glass fiber products. The contents of free, metastable, and bonded components on the surface of glass fibers dried at 125℃ are 0.17%, 0.14%, and 0.07%, respectively; while the contents of free, metastable, and bonded components on the surface of glass fibers dried at 115℃ are 0.21%, 0.16%, and 0.03%, respectively. The contents of free and metastable components of the sizing agent on the surface of glass fibers dried at 125℃ are lower than those on those dried at 115℃; however, the contents of bonded components of the sizing agent on the surface of glass fibers dried at 125℃ are higher than those on those dried at 115℃. Since the bonded component of the sizing agent is usually a silane coupling agent, the surface of glass fibers dried at 125℃ has a higher content of silane coupling agent.
[0053] Then, by combining the content of different components of the surface sizing agent and the interfacial strength of the glass fiber products, the influence of different components on interfacial reinforcement was analyzed to help researchers clarify the reinforcement mechanism. During the solvent separation process, the transverse fiber bundle tensile strength of the surface sizing agent in glass fibers dried at 125℃ was higher than that in glass fibers dried at 115℃. The content of free and metastable components in the surface sizing agent of glass fibers dried at 125℃ was lower than that of glass fibers dried at 115℃, while the content of bonded components was higher. These results indicate that the bonded components in the sizing agent are key to the bonding strength between glass fibers and resin. The bonded components connect the glass fibers through chemical bonds, promoting stress transfer at the glass fiber / resin interface. Glass fibers dried at 125℃ exhibit higher bonding strength between glass fibers and resin and have a higher content of bonded components. Based on these conclusions, 125℃ should be selected as the drying temperature for glass fiber production.
[0054] Example 3
[0055] A method for determining the bond strength between glass fiber and resin includes the following steps:
[0056] (1) After melting, drawing, and cooling the glass raw material with water mist, glass fiber filaments with a diameter of approximately 16 μm are obtained. Immediately afterwards, the glass fiber filaments are sized with an epoxy-based glass fiber sizing agent. Then, the sized glass fiber filaments are bundled together using a bundling wheel to form a complete glass fiber bundle. The resulting glass fiber bundle is then wound into a roll at high speed to obtain an epoxy-based glass fiber yarn roll containing a large amount of moisture and sizing agent.
[0057] (2) The epoxy-based glass fiber yarn roll containing a large amount of moisture was dried at 125°C for 19 hours to obtain dried glass fiber; the dried glass fiber was placed in a muffle furnace at 620°C for 1 hour, and the mass of the glass fiber before and after calcination was weighed by an electronic balance. The mass loss before and after calcination was the total mass of the impregnating agent.
[0058] (3) The glass fiber dried at 125℃ for 19 hours was immersed in acetone for 100 minutes, and then dried in an oven to remove the acetone, resulting in acetone-soaked glass fiber. The mass of the glass fiber before and after immersion was weighed using an electronic balance. The mass difference was obtained by subtracting the mass after immersion from the mass before immersion. The mass difference was divided by the total mass of the sizing agent to obtain the free component content.
[0059] Acetone is removed by rotary evaporation, and the free components of the glass fiber surface wetting agent are collected. The free components of the glass fiber surface wetting agent typically include film-forming agents, lubricants, and antistatic agents.
[0060] (4) The glass fibers soaked in acetone were extracted in a Soxhlet extractor for 24 hours using acetone as the solvent. After extraction, the acetone was removed by drying in an oven to obtain the Soxhlet-extracted glass fibers. The mass of the glass fibers before and after Soxhlet extraction was weighed using an electronic balance. The mass difference was obtained by subtracting the mass after soaking from the mass before soaking. The mass difference divided by the total mass of the sizing agent was the content of the metastable component. The low-boiling-point organic solvent was removed by rotary evaporation, and the metastable component of the sizing agent on the glass fiber surface was collected. The metastable component of the sizing agent on the glass fiber surface is usually an oligomeric silane coupling agent and a film-forming agent that interacts non-covalently with the coupling agent.
[0061] (5) The glass fibers dried by Soxhlet extraction for 19 hours were soaked in hot water at 100°C for 3 hours. After that, they were heated in an oven at 120°C for 2 hours to remove moisture, and water-extracted glass fibers were obtained. The mass of the glass fibers before and after soaking was weighed using an electronic balance. The mass difference was obtained by subtracting the mass after soaking from the mass before soaking. The mass difference divided by the total mass of the sizing agent was the content of the bonding component. The moisture was removed by freeze drying, and the bonding component of the sizing agent on the surface of the glass fibers was collected. The bonding component on the surface of the glass fibers is usually a coupling agent.
[0062] Example 4
[0063] Similar to Example 3, except that in step (2), the glass fiber dried at 125°C for 23 hours is soaked in acetone for 100 minutes, and then dried in an oven to remove the acetone, thus obtaining acetone-soaked glass fiber. The mass of the glass fiber before and after soaking is weighed using an electronic balance, and the percentage of mass loss can be calculated.
[0064] This invention compares glass fiber products dried at 125°C for 19 hours and 23 hours, respectively, to study the effect of drying time on the surface sizing agent composition of glass fiber and the bonding strength between glass fiber and resin. Figure 2 The sizing agent content of glass fiber surfaces dried at 125℃ for 19 hours and 125℃ for 23 hours, respectively ( Figure 2 (a and c) and the tensile strength of glass fiber / resin transverse fiber bundles ( Figure 2 (b and d).
[0065] Specifically, experiments can first determine the content of free, metastable, and bonded components of the sizing agent on the surface of different glass fiber products. The contents of free, metastable, and bonded components on the surface of glass fibers dried at 125℃ for 19 hours were 0.19%, 0.14%, and 0.06%, respectively; the contents of free, metastable, and bonded components on the surface of glass fibers dried at 125℃ for 23 hours were 0.16%, 0.16%, and 0.08%, respectively. The contents of metastable and bonded components of the sizing agent on the surface of glass fibers dried at 125℃ for 19 hours were lower than those on glass fibers dried at 125℃ for 23 hours.
[0066] Then, by combining the content of different components of the surface sizing agent and the interfacial strength of the glass fiber products, the influence of different components on interfacial reinforcement was analyzed to help researchers clarify the reinforcement mechanism. During solvent separation, the transverse fiber bundle tensile strength of the surface sizing agent in glass fibers dried at 125℃ for 23 hours was higher than that in glass fibers dried at 125℃ for 19 hours. The content of metastable and bonding components in the surface sizing agent of glass fibers dried at 125℃ for 19 hours was lower than that in glass fibers dried at 125℃ for 23 hours. Under the same temperature conditions, extending the drying time helps to increase the content of bonding components. Glass fibers dried at 125℃ for 23 hours exhibit higher bonding strength between the glass fiber and resin and a higher content of bonding components. Based on these conclusions, a drying process of 125℃ for 23 hours should be selected for the production of glass fibers.
[0067] The above description only illustrates the preferred embodiments of the present invention and should not be construed as limiting the scope of the claims. The present invention is not limited to the above embodiments, and variations in its specific structure are permitted. All modifications made within the scope of the independent claims of this invention are also within the scope of protection of this invention.
[0068] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
Claims
1. A method for determining the bonding strength between glass fiber and resin, characterized in that, Includes the following steps: (1) Dry the glass fiber coated with sizing agent to obtain dried glass fiber 1; place the dried glass fiber at 620℃ for 1 hour, and the mass loss before and after calcination is the mass of sizing agent; (2) The dried glass fiber 1 is soaked in a low-boiling-point organic solvent and then dried to obtain glass fiber 2. The mass difference between glass fiber 2 and dried glass fiber 1 divided by the mass of the sizing agent is the free component content. (3) Glass fiber 2 is extracted by Soxhlet and then dried to obtain glass fiber 3. The mass difference between glass fiber 3 and glass fiber 2 is divided by the mass of the sizing agent to obtain the content of metastable component. (4) After soaking glass fiber 3 in hot water, it is dried to obtain glass fiber 4. The difference in mass between glass fiber 4 and glass fiber 3 divided by the mass of sizing agent is the content of bonding component. (5) Test the transverse fiber bundle tensile strength of each of glass fiber 1, glass fiber 2, glass fiber 3 and glass fiber 4 with the resin, and determine the influence of the content of free component, metastable component and bonding component on the bonding strength between glass fiber and resin.
2. The method for determining the bonding strength between glass fiber and resin according to claim 1, characterized in that, In step (1), the drying temperature is 110-130℃ and the time is 19-23 hours.
3. The method for determining the bonding strength between glass fiber and resin according to claim 1, characterized in that, In step (1), the diameter of the glass fiber monofilament is 8-30 μm.
4. The method for determining the bonding strength between glass fiber and resin according to claim 1, characterized in that, In steps (2) and (3), the low-boiling-point organic solvent is acetone, n-hexane, dichloromethane, chloroform, tetrahydrofuran, ethanol, or methanol.
5. The method for determining the bonding strength between glass fiber and resin according to claim 1, characterized in that, In step (2), the soaking time is 10-100 minutes.
6. The method for determining the bonding strength between glass fiber and resin according to claim 1, characterized in that, In step (3), the Soxhlet extraction time is 2-48 hours.
7. The method for determining the bonding strength between glass fiber and resin according to claim 1, characterized in that, In step (4), the temperature of the hot water is 80-100℃, and the soaking time is 1-10 hours.
8. The method for determining the bonding strength between glass fiber and resin according to claim 1, characterized in that, The process for testing the transverse fiber bundle tensile strength of each of glass fibers 1, 2, 3 and 4 with resin is as follows: epoxy resin is mixed with polyetheramine to obtain pre-cured resin. Glass fibers 1, 2, 3 or 4 are placed in the middle position, and pre-cured resin is placed on both sides of glass fibers 1, 2, 3 or 4. Then, the mixture is cured to obtain a composite material specimen. The transverse fiber bundle tensile test is performed on the composite material specimen.
9. The method for determining the bonding strength between glass fiber and resin according to claim 8, characterized in that, The mass ratio of epoxy resin to polyetheramine is 100:
55.
10. The method for determining the bonding strength between glass fiber and resin according to claim 8, characterized in that, The curing process is as follows: keep at 100℃ for 1 hour, then keep at 140℃ for 1 hour, and finally keep at 180℃ for 2 hours.
Citation Information
Patent Citations
Quantitative analysis method of glass fiber surface impregnating compound
CN102564991A
Surface modification glass fiber and preparation method and application thereof
CN103183844A